Earth-Like: an education & outreach tool for exploring the diversity of planets like our own. Issue 3 (13th June 2020) - Tasker, Elizabeth J.; Ishimaru, Kana; Guttenberg, Nicholas; Foriel, Julien
Abstract: Earth-Like is an interactive website and twitter bot that allows users to explore changes in the average global surface temperature of an Earth-like planet due to variations in the surface oceans and emerged land coverage, rate of volcanism (degassing) and the level of the received solar radiation. The temperature is calculated using a simple carbon–silicate cycle model to change the level of CO2 in the atmosphere based on the chosen parameters. The model can achieve a temperature range exceeding −100°C to 100°C by varying all three parameters, including freeze-thaw cycles for a planet with our present-day volcanism rate and emerged land fraction situated at the outer edge of the habitable zone. To increase engagement, the planet is visualized by using a neural network to render an animated globe, based on the calculated average surface temperature and chosen values for land fraction and volcanism. The website and bot can be found at earthlike.world and on twitter as @earthlikeworld . Initial feedback via a user survey suggested that Earth-Like is effective at demonstrating that minor changes in planetary properties can strongly impact the surface environment. The goal of the project is to increase understanding of the challenges we face in finding another habitable planet due to the likely diversity of conditions on rocky worlds within our Galaxy.